2019
DOI: 10.1016/j.cegh.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Fat structure and composition in human milk and infant formulas: Implications in infant health

Abstract: Infants are frequently vulnerable to transient functional gastrointestinal disorders (FGIDs) including constipation. Evidence suggests stool frequency and consistency depends upon the various nutritional components including fats. Long chain saturated fats esterified at the sn-1 and sn-3 positions seen in vegetable oil-based infant formulas, are associated with the formation of calcium fatty acid soaps, contributing to constipation. Moreover, fatty acids esterified at sn-2 position, seen in breast milk, lead t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 36 publications
(45 reference statements)
0
13
0
3
Order By: Relevance
“…Studies have shown that this specific position of triglycerides in palmitic acid improves the absorption of both palmitic acid and macro-elements such as calcium and magnesium. This improved absorption decreases constipation and enhances the BF infant's intestinal well-being [64,65].…”
Section: Lipidsmentioning
confidence: 99%
“…Studies have shown that this specific position of triglycerides in palmitic acid improves the absorption of both palmitic acid and macro-elements such as calcium and magnesium. This improved absorption decreases constipation and enhances the BF infant's intestinal well-being [64,65].…”
Section: Lipidsmentioning
confidence: 99%
“…29 O ácido oleico (AO, 18:1n-9) é o AG predominante dentre os ácidos graxos monoinsaturados (AGMIs) do LH, sendo considerado um AG marcador do leite maduro, utilizado pelo neonato principalmente como fonte energética, além de favorecer a absorção de gordura pelo intestino delgado e a mielinização dos axônios. 22,10,25,30 Dentre os ácidos graxos saturados (AGSs) do LH, o ácido palmítico (AP, 16:0) é o majoritário. Este AG apresenta efeitos analgésicos por elevar os níveis de anandamida, neurotransmissor responsável pela ligação endógena que ocorre em receptores canabinóides do cérebro, podendo produzir sedação.…”
Section: Lipídios Presentes No Glóbulo De Gordura Do Leite Humanounclassified
“…It is located in the TAG sn-2 region, simplifying the pancreatic lipase action that specifically hydrolyzes the FA at the sn-1 and sn-3 positions converting the palmitic acid to sn-2 MAG, which is generally well absorbed resulting in improvement of intestinal discomfort, decreasing colic and crying of the newborn. [25] In addition, the palmitic acid position influences the n-acylentanolamides, including levels of anandamide, which presents analgesic effects contributing to the enlightenment of the association between the palmitic acid position and the baby cry behavior [14].…”
Section: Importance Of Fatty Acids In Human Milkmentioning
confidence: 99%